A importância do programa nacional de assistência estudantil para a permanência e o êxito acadêmico de estudantes cotistas no Instituto Federal de Educação da Paraíba - Pordeus, Angélica Gadelha (2019)
The present work has as its theme the Student Assistance Policy and the Quota System within the scope of the Federal Institute of Education of Paraíba - IFPB. The general objective was to analyze the importance of the National Program of Student Assistance - PNAES, implemented in the IFPB through the Student Assistance Policy, for the permanence and academic success of the student by quotas, with a view to the realization of rights. The intention was to make an analysis about the changes in performance, with an evaluation of its execution and relevant from the access to the speech, recording their expectations and provoking a critical debate about the conduct of such actions in the Institution. The delimitation of the course begins a historical part with the objective of carrying out a historical study on the evolution of the period 2003-2010, focusing on the PNAES. The Federal School of Vocational Education and the Policies of Quotas and Student Assistance, implemented and executed in the IFPB. The evaluation of the study in the survey method, the method in the historical performance, using the exploratory study, on the method, based on historical method. The field research was applied to the Bachelor of Electrical Engineering and the Degree in Chemistry of the IFPB, Campus João Pessoa, on the policy of student education and the system of admission by quotas. A questionnaire was used for the execution of data, which expressed ideas, needs and suggestions to improve and complement an existing policy. The results of this test were therefore necessary to identify the needs of the students that are directed to the relevant sectors, as well as, will be sent to the Rectory of Student Affairs (PRAE) of the IFP. . In the presented scenario, the importance of strengthening actions in attempts to attenuate as social unfoldings with a social, human, educational and cultural vision of the country stands out.